Light-enabled intramolecular [2 + 2] cycloaddition via photoactivation of simple alkenylboronic esters - Lewis McGhie; Hannah M. Kortman; Jenna Rumpf; Peter H. Seeberger; John J. Molloy (Beilstein Journal of Organic Chemistry)
The photoactivation of organic molecules via energy transfer (EnT) catalysis is often limited to conjugated systems that have low-energy triplet excited states, with simple alkenes remaining an intractable challenge. The ability to address this limitation, using high energy sensitizers, would represent an attractive platform for future reaction design. Here, we disclose the photoactivation of simple alkenylboronic esters established using alkene scrambling as a rapid reaction probe to identify a suitable catalyst and boron motif. Cyclic voltammetry, UV–vis analysis, and control reactions support sensitization, enabling an intramolecular [2 + 2] cycloaddition to be realized accessing 3D bicyclic fragments containing a boron handle.